Debatter og reguleringer af muslimske tørklæde – populisme og symboler - Andreassen, Rikke; Siim, Birte (Politik, 2010)
The article illustrates how the Muslim headscarf has become a symbol of a struggle about liberal principles and values connected with democracy, gender and equality and how it is used by populist forces as symbolic politics in order to promote a more restrictive immigration- and integration policy. In addition, it shows how key actors have employed democracy and gender equality as arguments both for and against the right to wear headscarves. Taking the point of departure in the headscarf debate the authors argue that it has become a normative democratic challenge to accommodate the diversity of cultural and religious minorities and develop a multidimensional equality politics, which integrates principles of ethnic equality with gender equality.